Imidazolium-Based Anion Exchange Membranes for Alkaline Anion Fuel Cells: Interplay between Morphology and Anion Transport Behavior. Issue 8 (1st January 2019) - Zhao, Yue; Yoshimura, Kimio; Takamatsu, Harufumi; Hiroki, Akihiro; Kishiyama, Yoshihiro; Shishitani, Hideyuki; Yamaguchi, Susumu; Tanaka, Hirohisa; Koizumi, Satoshi; Radulescu, Aurel; Appavou, Marie-Sousai; Maekawa, Yasunari
Abstract : We studied anion transport behaviors in grafted anion exchange membranes (AEMs) composed of 2-methyl- N -vinylimidazole (Im) and styrene (St) having various Im/St ratios (6/4, 4/6, and 3/7) grafted onto poly(ethylene- co -tetrafluoroethylene) films (named AEM64, AEM46, and AEM37). The transport properties were evaluated based on the transport efficiency defined as ratios of anion diffusion coefficients in AEMs to dilution solutions (D/D0 ) and were correlated to the morphology of AEMs analyzed by the small angle scattering method. We found a master curve of D/D0  with hydration for AEM64, regardless of the grafting degree and anion species; however, D/D0 for AEM46 and AEM37 was similar with AEM64 at low hydration conditions, but clearly deviated down from it at high hydration conditions. Such difference could be elucidated by the membrane morphology. For AEM64, the conducting phase was homogeneous comprised dispersed ions, and the conductivity correlated well with the increasing hydration. In contrast, when the styrene content increased (i.e., AEM46 and AEM37), the conducting phase changed to heterogeneous with water puddles separated from dispersed ions, and the anion transport was suppressed. Results in this work gave a mechanistic insight in the anion transport properties in proximity of the AEM morphology at various hydration conditions.